Corporate governance and bank capitalization strategies - Anginer, Deniz; Demirguc-Kunt, Asli; Huizinga, Harry; Ma, Kebin (Journal of Financial Intermediation, 2016)
Abstract This paper examines the relationship between banks’ capitalization strategies and their corporate governance and executive compensation schemes for an international sample of banks over the 2003–2011 period. Shareholder-friendly corporate governance, in the form of a separation of the CEO and chairman of the board roles, intermediate board size, and an absence of anti-takeover provisions, is associated with lower bank capitalization, consistent with shareholder incentives to shift risk towards the financial safety net. Higher values of executive option and stock wealth invested in the bank are associated with higher capitalization as a potential reflection of executive risk aversion, but the risk-taking incentives embedded in executive compensation packages are associated with lower capitalization.